2017
DOI: 10.1186/s13052-017-0357-9
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of oral propranolol for infantile hemangiomas started before 5 weeks and after 5 months of age: an Italian multicenter experience

Abstract: BackgroundDespite not being licensed for the treatment of infantile hemangiomas (IH) in infants younger than 5 weeks or older than 5 months, propranolol is often used in these age groups to prevent or to treat potentially severe complications. The objective of the present study was to review the experience of 8 Italian pediatric and dermatologic centers regarding propranolol treatment for IH started before 5 weeks or after 5 months of age.MethodsWe retrospectively reviewed the records of patients followed up f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…A study also showed that younger age, premature birth, and lower BW are associated with intolerable AEs [8]. On the contrary, starting age of younger than 5 weeks dose not lead to more AEs, compared with starting age of older than 5 months [35]. Our study showed that starting age of no older than 3 months led to more AEs in the CNS, and starting age of older than 3 months was a protective factor against side effects in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…A study also showed that younger age, premature birth, and lower BW are associated with intolerable AEs [8]. On the contrary, starting age of younger than 5 weeks dose not lead to more AEs, compared with starting age of older than 5 months [35]. Our study showed that starting age of no older than 3 months led to more AEs in the CNS, and starting age of older than 3 months was a protective factor against side effects in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients treated with systemic beta-blockers for IHs is expected to grow and some clinicians might even consider offering this effective treatment to children beyond the proliferation phase. In fact off-label use of propranolol after 5 months of age (as for our case) has frequently been described as successful in the literature [ 14 17 ]. The experience with this drug is therefore accumulating and we will gain more and more information on its effectiveness [ 18 ] and its possible side effects.…”
Section: Discussionmentioning
confidence: 85%
“…12 Since then, three RTC and nine observational studies demonstrated a high safety profile of OP, [13][14][15][16][17][18][19][20] acceptable before 5 weeks and after 5 months of age. 21 OP is currently recommended as first-line treatment for proliferative phase IHs meeting the following criteria: 22 IHs causing/likely to cause visual impairment and potential or actual obstruction of the nasal cavity/airway/auditory canal, potential or actual functional impairment and/or lip deformities, IHs which develop ulceration or cause recurrent infection, organ compression (liver and spinal cord) and risk of permanent disfigurement.…”
Section: Introductionmentioning
confidence: 99%